(untitled) (Nigerian Journal of Cooperative Economics and Management, 2026)
Agricultural cooperatives play a critical role in improving the productivity and livelihoods of smallholder farmers through improved access to farm inputs, collective marketing, extension support, and economies of scale. Despite these potentials, empirical evidence on the extent to which agricultural cooperatives contribute to sustainable farm performance among smallholder farmers in Ayamelum Local Government Area of Anambra State remains limited. This study therefore examined the contributions of agricultural cooperative societies to sustainable farm performance of smallholder farmers in Ayamelum local government area, Anambra State, Nigeria. The population of this study comprises of all active farmers’ cooperative societies in Ayamelum local government area of Anambra State. There are 37 registered farmers cooperatives in the study area with a membership strength of 482. The sample size used was 219 cooperative members using Taro Yamane formular. Objectives were processed using descriptive statistics (like percentage, mean and standard deviation) and the regression model of the Ordinary Least Square (OLS). T-test and F-test statistics were used to test the hypotheses of the study and the overall fitness of the model. All the analyses were done using SPSS version 23. Linear regression model of the Ordinary Least Square (OLS) approach was used to analyze the objectives. The regression model is significant at .000 which is less than 0.05 thus confirming that cooperative member’s farm performance in the area was dependent on farm inputs obtained and value of agricultural products marketed through cooperative. It was concluded from the findings of the study, that cooperative significantly affects the performance of smallholder farmers in Agricultural zone of Anambra State. Based on the findings of the study the researcher recommends among others that cooperative society should endeavor to meet the farm input needs of the farmers so as to increase their yield, their profit and also improve their performance and Anambra State government should encourage research, development and extension of adequate extension services to smallholder farmers through the Ministry in charge of cooperative in the state.